The Share of Genetic and Environmental Factors in Determination of Dermatoglyphic Variability - Budnik, Alicja (Anthropological Review, 1981)
The author has applied analysis of variance procedures to quantitative dermatoglyphic traits: finger ridge counts and interdigital ridge counts (a-b, b-c, c-d as well as their sum a-d). The material comprises finger and palm prints of both hands of about 200 males. The analysis of variance is based on an assertion that differences between two antimeres of the same individual may be formally treated as those between monozygotic twins, since regular asymmetry is very slight. Appropriate for such an approach, partitioning of variance into components resulting from various sources is as follows: VP=VG+VEg+VEs+VEr where: VP — total observed (phenotypical) variance, VG — genetic variance that can be further partitioned into components due to additive, dominance, epistatic. etc. effects of alleles and their interactions, VEg — interindividual environmental variance, VEs — within-individual environmental variance, VEr. variance of random error of measurement (observation). From correlation coefficients of characters of left and right hand the author obtains an estimate of "heritability sensu lato”: \[ r = V_g + E_Eg V_p \] Comparing this estimate with estimates of “true heritability” (h2=Va/Vp) allows to estimate share of dominance + epistatic variance as well as Veg in total phenotypic variance. In order to evaluate genetic polymorphism of quantitative dermatoglyphic traits and their ecosensitivity appropriate parts of variance are expressed in units of mean trait values yielding indices of ”genetic polymorphism” — P, and ”ecosensitivity” D, as described by Henneberg and Lewicki (1978). Arithmetic means, total variances, estimates of parts of variance and above mentioned indices are presented in tables 1-3. Values of correlation coefficients between right and left hand are comparable with classical heritability estimates obtained on twins and families by a number of authors. Genetic polymorphism in dermatoglyphic traits is considerably higher than that observed in human body dimensions. However, what has not been stressed enough by other authors, also ecosensitivity of dermatoglyphes tourns out to be considerable — much higher than that observed for anthropometric characters. The author shows that values of components of variance and indices of polymorphism and ecosensitivity are considerably influenced by definitions of characters — changing rules of counting ridges in whorls. This leads to a suggestion that ridge counts and dermatoglyphic patterns may constitute separate, to a large extent unrelated, properties of ridged skin.